Genetic variation in the bioactivation pathway for polycyclic hydrocarbons and heterocyclic amines in relation to risk of colorectal neoplasia - Wang, Hansong; Yamamoto, Jennifer F; Caberto, Christian; Saltzman, Barbara; Decker, Robert; Vogt, Thomas M; Yokochi, Lance; Chanock, Stephen; Wilkens, Lynne R; Le Marchand, Loïc (Carcinogenesis (New York), 2011)
Animal work implicates chemical carcinogens, such as polycyclic aromatic hydrocarbons (PAHs) and heterocyclic aromatic amines (HAAs) as contributing to the development of colorectal cancer (CRC). The epidemiologic evidence, however, remains inconsistent possibly due to intra-individual variation in bioactivation of these compounds. We conducted a case-control study of colorectal adenoma (914 cases, 1185 controls) and CRC (496 cases, 607 controls) among Japanese Americans, European Americans and Native Hawaiians to investigate the association of genetic variation in the PAH and HAA bioactivation pathway (CYP1A1, CYP1A2, CYP1B1, AHR and ARNT) identified through sequencing with risk of colorectal neoplasia, as well as their interactions with smoking and intakes of red meat and HAAs. The A allele for ARNT rs12410394 was significantly inversely associated with CRC [odds ratios (ORs) and 95% confidence intervals (CIs) for GG, AG and AA genotypes: 1.00, 0.66 (0.48-0.89), 0.54 (0.37-0.78), P(trend) = 0.0008] after multiple comparison adjustment. CYP1A2 rs11072508 was marginally significantly associated with CRC, where each copy of the T allele was associated with reduced risk (OR: 0.72, 95% CI: 0.58-0.88, P(trend) = 0.0017). No heterogeneity of genetic effects across racial/ethnic groups was detected. In addition, no significant interaction was observed after adjusting for multiple testing between genetic variants and pack-years of smoking, intake of red meat or HAAs (PhIP, MeIQx, Di-MeIQx or total HAAs) or NAT2 genotype (Rapid versus Slow or Intermediate). This study suggests that the genomic region around ARNT rs12410394 may harbor variants associated with CRC.